222k views
3 votes
Simplify the following expression:
3x (7x-4)-(x-8)

2 Answers

4 votes

Answer:


=21x^(2) -13x+8

Explanation:

User Allejo
by
5.4k points
2 votes

Answer:

=21x2−13x+8

Explanation:

=3x(7x−4)+−1(x−8)

=3x(7x−4)+−1x+(−1)(−8)

=3x(7x−4)+−x+8

Distribute:

=(3x)(7x)+(3x)(−4)+−x+8

=21x2+−12x+−x+8

Combine Like Terms:

=21x2+−12x+−x+8

=(21x2)+(−12x+−x)+(8)

=21x2+−13x+8

User Ovo
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.